Variability of upland rice genotypes response to low light intensity - ARIS HAIRMANSIS; YULLIANIDA YULLIANIDA; SUPARTOPO SUPARTOPO; ALI JAMIL; SUWARNO SUWARNO (Society for Indonesian Biodiversity, 2017)
Hairmansis A, Yullianida, Supartopo, Jamil A, Suwarno. 2017. Variability of upland rice genotypes response to low light intensity. Biodiversitas 18: 1122-1129. Plantation areas have a great potential to be utilized for upland rice production through intercropping. One of major constraints in the cultivation of upland rice as intercropping is low light intensity caused by shading. Improvement of rice varieties for shading tolerance is therefore important to increase rice production in upland areas. The objective of this study was to investigate the variability of upland rice genotypes responses to shading and identify the best genotypes for intercropping rice cultivation. Thirty-eight upland rice breeding lines, the shading tolerant rice variety Jatiluhur, and the shading susceptible rice variety IR64 were evaluated for their response to low light intensity in the greenhouse and the field. Greenhouse screening was conducted to determine their shading tolerance in vegetative stage while evaluation in the field was performed to evaluate their agronomic performance under 55% shading and normal conditions. Variation in upland rice genotypes on low light stress was revealed both in greenhouse and field trials. In the greenhouse trial, 12 genotypes showed higher survival rate compared to tolerant rice variety Jatiluhur. Field evaluation demonstrated that 55% shading increased plant height, reduced productive tiller number, delayed flowering time, increased spikelet sterility and reduced grain yield. Upland rice breeding line B11908F-TB-3-WN-1 showed high yield relative in shading condition compared to normal condition and had high-stress tolerance index (STI) which indicated the genotype was tolerant to shading.